PENGARUH KEPUASAN KONSUMEN DAN DISKON TERHADAP VOLUME PENJUALAN PT. ATMINDO TBK TANJUNG MORAWA - Geraldo Fransiskho; Thomas Sumarsan Goh; Wily Julitawaty (STIE-PMCI, 2021)
Consumer satisfaction is a measurement of consumers or users of company products or services who are very happy with the products or services received. Discounts are discounts given by marketers to consumers as a reward for certain activities of a pleasant purchase for marketers. Sales volume is an achievement that is expressed quantitatively from a physical point of view of a product and is something that indicates the ups and downs of sales which are expressed in terms of units, kilos, tonnes or liters.This research uses descriptive quantitative research. The data analysis technique used in this study is multiple linear regression analysis. The measurement scale used is a Likert scale. Simultaneously, there is a significant influence between customer satisfaction and discount variables on sales volume. While partially found that the customer satisfaction variable has a significant effect on sales volume. Partially found that the discount variable has a significant effect on sales volume.Â Keywords: Customer Satisfaction, Discounts, Sales Volume